Use of Secondary Cellulose Fibers as a Replacement for the Basic Components of Core Insulators of Vacuum Insulation Panels - Jiří Zach; Jitka Peterková; Vítězslav Novák; Mitja Košir; David Božiček (Recycling, 2025)
The ever-increasing requirements in the field of energy efficiency of buildings imply the necessity of using an ever-increasing amount of insulation in building structures. However, together with the requirements of the new EPBD directive EU/2024/1275, it is also necessary to monitor the carbon footprint of individual materials incorporated into the building structure. The aim of the research work is to substitute primary raw materials used for the production of vacuum insulation panels (VIPs) with secondary cellulose fibers produced by recycling newsprint. Five recipes were proposed to verify the substitution effect for individual key raw materials of core insulation for VIPs. Key (primarily thermal insulation) properties were determined on laboratory-produced samples, and it was found that the proposed hybrid core insulations with secondary cellulose fibers from recycled newsprint exhibit very favorable properties and could be used for the production of VIPs used in building structures.